Are the Outcomes of Minimally Invasive Transforaminal/Posterior Lumbar Fusion Influenced by the Patient's Age or BMI?. Issue 7 (August 2020) - Manson, Neil; Hubbe, Ulrich; Pereira, Paulo; Lam, Khai; Fuster, Salvador; Senker, Wolfgang
Abstract : Study Design: A retrospective subgroup analysis of a prospective observational study was carried out. Summary of Background Data: Patients' baseline characteristics may influence the clinical outcomes after minimally invasive lumbar interbody fusion (MILIF). Objective: This study aimed to investigate the influence of patient's age and body mass index (BMI) on the clinical outcomes of MILIF for degenerative lumbar disorder. Materials and Methods: A total of 252 patients underwent MILIF. The clinical outcomes, including time to first ambulation, time to postsurgical recovery, back/leg pain in visual analog scale, Oswestry Disability Index, and EuroQol-5 Dimension, were collected at baseline, 4 weeks, 6, and 12 months. Patients were subgrouped by age (50 y and below: N=102; 51–64 y: N=102; 65 y and above: N=48) and BMI (⩽25.0: N=79; 25.1–29.9: N=104; ≥30.0: N=69). Data from baseline to 12 months were compared for all clinical outcomes within age/BMI subgroups. Adverse events (AEs) and serious adverse events (SAEs) were summarized by age and BMI subgroups. Results: All age and BMI subgroups showed significant improvements in clinical outcomes at 12 months compared with the baseline. The median time to first ambulation was similar for all subgroups (age groups: P =0.8707; BMI: P =0.1013); older people show a trend of having longer time to postsurgical recovery (age groups: P =0.0662; BMI: P =0.1591). Oswestry Disability Index, back, and leg pain visual analog scale, and EuroQol-5 Dimension were similar in all subgroups at every timepoint. A total of 50 AEs (N=39) were reported, 9 of which were SAEs; 3 AEs and 1 SAE were considered to be related to surgical procedure. No differences were observed in safety by age groups and BMI groups. Conclusion: MILIF appears to be safe and effective, independent of age or weight in the treatment of degenerative lumbar disorder. Level of Evidence: Level II.